Enhanced photocatalytic performance of ZnSe/PANI nanocomposites for degradation of organic and inorganic pollutants - Shirmardi, Abbas; Teridi, Mohd Asri Mat; Azimi, Hassan Rayat; Basirun, Wan Jefrey; Jamali-Sheini, Farid; Yousefi, Ramin (Elsevier, 2018)
Current work presents a study about the effect of polyaniline (PANI) as an organic semiconductor on the photocatalytic performance of ZnSe nanoparticles (NPs). Pristine ZnSe NPs and ZnSe/PANI nanocomposites were synthesized by a simple and cost-effective co-precipitation method in the ambient conditions. X-ray diffraction (XRD), Raman, and Fourier-transform infrared spectroscopy (FTIR) results confirmed that, a heterojunction was created by ZnSe NPs and PANI composite. High-resolution transmission electron microscopy (HRTEM) image showed that the NPs were deposited by PANI completely and a core-shell structure was generated by ZnSe and PANI. Photoluminescence (PL) spectroscopy results showed the optical properties of the pristine ZnSe NPs and ZnSe/PANI nanocomposites were similar with lower defect emission intensity for the ZnSe/PANI nanocomposites. However, the PL and UV–Vis results revealed that, the PANI caused a decrease in band-gap value of the ZnSe/PANI nanocomposites in compared to the band-gap value of the pristine ZnSe NPs. In addition, X-ray photoelectron spectroscopy (XPS) results indicated that, the PANI caused a shift in the valance band (VB) and conduction band (CB) edges of ZnSe/PANI nanocomposites in compared with pristine ZnSe NPS. Finally, the photocatalytic performance of the products for removing of methylene blue (MB) and chromate ions was examined under a visible-light source irradiation. An enhancement photocatalytic performance for ZnSe/PANI nanocomposites in compared to the pristine ZnSe NPs was observed. Brunauer–Emmett–Teller (BET) results indicated that textural properties of the nanocomposites were decreased by PANI. According to the optical properties and band gap-value of the products a type-II heterojunction was created by band alignment of the ZnSe and PANI and such heterojunction was the most important factor for the enhancement photocatalytic performance of the ZnSe/PANI nanocomposites in compared to the photocatalytic activity of the pristine ZnSe NPs.